Nanosatellite on attitude determination and control software development - Chua, Zheng Sheng (2019)
Satellites are important communication devices which are used to transmit countless of information from point to point in our everyday lives. There are a lot of space debris that is manoeuvring around the space. In order to prevent collision of these space junk, Attitude Determination and Control Subsystem (ADCS) has been used to determine and orient the Satellite towards a provided direction. However, software that has been utilised in the commercial world often holds a hefty price tag. This paper seeks to explore alternative solutions to predict the future position of the Satellite at a lower cost and to achieve the same objective. Some solutions which have been discovered and will be further discussed in this paper are SGP4 Propagator and Two-Line Elements. Another solution proposed is a disturbance calculator which can be used to calculate the approximate pressure in space that will affect the trajectory of a Satellite.